التسويق السياحي كمتطلب استراتيجي لتحقيق تنمية سياحية مستدامة في ظل سياسة التنويع الاقتصادي بالجزائر - العلمي، إيمان; زرقين، عبود (مركز البحث وتطوير الموارد البشرية - رماح, 2017)
tourism marketing received the hugestpart of importance fromacademics and practitionals in the field of tourism, becauseit has severe influence in getting and attractingaroundit. Algeriais one of the country which pays attention and focuses to the importance to practice tourism . tobe aneconomical alternative to fuels and itadopts for thispurpose a the strategy to upgrade tourism and itsdevelopment for the sake of marketing the touristicproducerwhodiffersfromothers by effeciencyconcerning. monuments, remnantand heritagein addition to promotionaltouristicamenities in variouscities of Algeria. Throughthisreferential, wedealtto studytourism marketing and the reality of sustainabletourismdevelopment in Algeria via projecting on the major measures toensur the realization of sustainable tourism development.
حضي التسويق السياحي باهتمام كبير من طرف الأكاديميين والممارسين في مجال السياحة، لما له من تأثير بالغ في تحصيل وجذب السياح في هذا الميدان، ومن ثم تنميته ككل، والجزائر من الدول التي انتبهت لأهمية صناعة السياحة وتسويقها لجعلها بديلا اقتصاديا للمحروقات، وقد تبنت لأجل ذلك إستراتجية محكمة لترقية السياحة وتنميتها من أجل تسويق المنتج السياحي الذي يتميز بالوفرة من حيث التراث والآثار والمرافق السياحة الترويحية في مختلف مدن ومناطق الجزائر. ومن خلال هذه المرجعية تطرقنا إلى دراسة التسويق السياحي وواقع التنمية السياحية المستدامة في الجزائر من خلال تسليط الضوء على أهم الإجراءات الكفيلة بتحقيق تنمية سياحية مستدامة.
Keywords: الجزائر -- التنمية المستدامة -- التنمية السياحية -- التسويق السياحي -- السياسة الاقتصادية